Analisis Karakteristik Konsumen Yang Berbelanja Sembilan Bahan Pokok (Sembako) Di Pasar Tradisional Dan Pasar Moderen Di Kecataman Wanokaka - Saratya, July; Novano Alrinta (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
The rapid expansion of modern retail in rural and suburban areas has created a market dualism that significantly influences community consumption patterns. This study aims to analyze the specific consumer characteristics associated with the preference for shopping for basic food commodities (Sembako) in traditional versus modern markets within the Wanokaka District. A descriptive-comparative quantitative method with a cross-sectional design was employed. A sample of 100 respondents was selected using the accidental sampling technique, utilizing structured questionnaires as the primary research instrument. Data analysis involved univariate analysis to describe respondent profiles and bivariate analysis using the Chi-Square test to examine the relationships between variables. The findings indicate a significant correlation between education level (p=0.000), income level (p=0.001), and age (p=0.004) with the choice of shopping location. Consumers with higher education, younger age, and middle-to-upper income levels tend to prefer modern markets due to factors such as environmental comfort, price transparency, and transaction efficiency. Conversely, traditional markets continue to dominate the low-income and older consumer segments, maintaining their relevance through price negotiability, flexible retail units, and strong social interactions. This study concludes that socio-economic characteristics are the primary predictors of market segmentation in Wanokaka. It is recommended that local governments prioritize the revitalization of traditional market infrastructure to ensure its competitiveness amidst the ongoing expansion of modern retail sectors